Financial Assessment of Potential Carbon Pricing Policy and Energy Transition Scenarios in Indonesia’s Nickel HPAL Project - Tio Gefien Imami; Ana Noveria (Journal Integration of Management Studies, 2026)
Indonesia’s mandate to achieve Net Zero Emissions (NZE) by 2060 exerts unprecedented pressure on energy-intensive mineral processing sectors to decarbonize while maintaining economic viability. While the macro-level implications of carbon policies are well documented, project-level financial responses to the simultaneous imposition of domestic carbon pricing (Nilai Ekonomi Karbon - NEK), the EU’s Carbon Border Adjustment Mechanism (CBAM), and renewable energy transition pathways remain underexplored. This study quantifies the financial resilience and risk profiles of a representative large-scale state-owned High-Pressure Acid Leach (HPAL) nickel project in Eastern Indonesia under diverse policy trajectories. A 20-year scenario-based Discounted Cash Flow (DCF) model was developed (WACC = 14.89%)  and integrated with Monte Carlo simulations to evaluate four configurations: (1) a gas-powered baseline; (2) gas subject to NEK; (3) gas subject to both NEK and CBAM; and (4) a solar-powered configuration incorporating NEK, CBAM, and a 10% carbon-offset allocation. Results demonstrate that while dual carbon-pricing regimes significantly compress project margins, transitioning to solar-powered operations curtails cumulative emissions and hedges against long-term regulatory volatility. Sensitivity analysis identifies nickel pricing, sales volume, and input costs as the primary determinants of valuation. Monte Carlo simulations reveal that the renewable configuration yields a more concentrated Net Present Value (NPV) distribution, indicating enhanced resilience amid extreme policy and price uncertainty. Ultimately, the project maintains financial viability across all scenarios, though performance depends on the architecture of international carbon regimes and energy procurement strategies. This research internalizes carbon-policy uncertainty into project-level capital budgeting, providing a framework for navigating the decarbonization of critical mineral value chains.